Du bon usage des pesticides : analyse socio-politique de la formation Certiphyto auprès des agriculteurs français - Sonia Grimbuhler; Elisabeth Marcotullio; Théo Werlen; Marc Delanoë; Jean-François Viel (VertigO)
Since 2009, all French professionals working with pesticides are required to hold the Certiphyto certificate, which attests to their sufficient knowledge to safely sell, advise on, or use pesticides and reduce their overall use. In parallel, public authorities have recorded not a decrease but an increase in national pesticide consumption, casting doubt on the relevance and effectiveness of this training. To address this issue, trainers and farmers who participated in 40 Certiphyto training courses agreed to have their sessions recorded. These recordings were analyzed quantitatively and qualitatively. Then, the « real » Certiphyto training, as observed through the recordings, was compared with the « prescribed » training as recommended by authorities. In quantitative terms, the average duration of the sessions is shorter than the guidelines. In qualitative terms, deviations from the prescribed standard are almost always present. Some topics are covered unnecessarily, while others that should be included are overlooked. A semantic analysis of the recordings also reveals inconsistencies in pedagogical approaches, a lack of emphasis on general prevention principles, and an excessive focus on technical and regulatory aspects. Based on these findings, it is clear that a redesign of the Certiphyto training is necessary to promote better pesticide use in France. Recommendations are developed and will need to be reviewed by stakeholders, translated into specific operational objectives, and ultimately implemented and validated according to each organization's unique timelines and priorities.